Simulation of shear behavior of corroded reinforced concrete beams flexurally repaired with steel fiber-reinforced concrete. (December 2021) - Van Hong Bui, Linh; Jongvivatsakul, Pitcha; Limpaninlachat, Pornpen; Stitmannaithum, Boonchai; Nguyen, Thanh-Truong; Nguyen, Trong-Phuoc
Abstract: The finite element (FE) method is a common and convenient tool for simulating the behaviors of reinforced concrete (RC) beams. However, the applicability of the FE method for simulating the structural responses of degraded RC beams repaired with steel fiber-reinforced concrete (SFRC) remains unclear. In this study, RC beams subjected to corrosion and repaired with SFRC were carefully studied, based on experimental investigations and FE modeling. Eight RC beams were initially subjected to a corrosion process before being repaired by SFRC in the flexural zone (tension region). The repaired beams were then subjected to four-point bending tests and numerical simulations to investigate their structural performances. The behaviors of the shear carrying capacity, load–deflection relationship, reinforcement strain, cracking and deformation mechanisms, and steel–SFRC/steel–concrete bond profiles were experimentally investigated and validated the predictive performances in the simulations. The results from the analyses demonstrated that the beams subjected to a high corrosion degree and repaired by SFRC with 2% of steel fiber volume resisted the largest crack openings. The failure of the SFRC-repaired beams tended to convert a brittle shear failure to a ductile failure through the yielding of the tensile reinforcement. An increase in the degree of corrosion reduced the bond efficiency between the corroded steel and SFRC. Furthermore, the effects of the SFRC stress–strain models on the performances of the SFRC-repaired members were investigated based on a parametric study. It was found that the efficiency of the FE simulation depends substantially on the characteristics of the material constitutive models and shear crack transfer coefficients. Finally, effective SFRC stress–strain models were suggested for simulating the responses of SFRC-repaired beams in ANSYS software.